Directing the Deformation Paths of Soft Metamaterials with Prescribed Asymmetric Units - Wu, Gaoxiang; Cho, Yigil; Choi, In-Suk; Ge, Dengteng; Li, Ju; Han, Heung Nam; Lubensky, Tom; Yang, Shu (WILEY-V C H VERLAG GMBH, 2015)
By prescribing asymmetric ligaments with different arrangements in elastomeric porous membranes of pre-twisted kagome lattices, the buckling instability is avoided, allowing for smooth and homogenous structural reconfiguration in a deterministic fashion. The stress-strain behaviors and negative Poisson's ratios can be tuned by the pre-twisting angles.
Keywords: NEGATIVE POISSONS RATIO; AUXETIC BEHAVIOR; PATTERN TRANSFORMATIONS; ELASTIC INSTABILITY; PERIODIC STRUCTURES; HYDROGEL MEMBRANES; SYMMETRY-BREAKING; PHOTONIC CRYSTAL; CELLULAR SOLIDS; SHAPE